Make my wish come true ebook - Lippincott, Rachael (2024)
"Forgiveness, friendship, and vulnerability all shine as brightly as holiday lights in this snow-sprinkled romance." — Booklist (starred review) 'Tis the season for holiday hijinks in this "swoon-worthy" ( Kirkus Reviews ) sapphic rom-com about a rising star and a small town girl going on twelve fake holidates from the New York Times bestselling authors of She Gets the Girl , Rachael Lippincott and Alyson Derrick! Twelve days of fake dates. Two holidays. One chance to convince everyone they're in love. Arden James is Hollywood's hottest teen actor. Infamously reckless, she's a constant in the tabloids. But when her messy reputation costs her an audition for her dream role, Arden and her publicist make up a lie to flip the script. Only, for the lie to work, she'll have to head home for the holidays for the first time in four years. Caroline Beckett has spent those last four years shining up a stellar portfolio that will get her into a top journalism program and convincing herself she could not be less interested in what her former best friend and first crush has been up to since she left without a word. But when Arden suddenly shows up at her doorstep with the promise of a real byline in Cosmopolitan in exchange for a write up on their "secret romance" and twelve snow-covered holidates in their Christmas-obsessed hometown, Caroline can't help but be tempted into playing along. It should be easy enough to stand each other for twelve days to make their dreams come true, right? But when old feelings start to bubble up, so do new holiday wishes that might just have Arden and Caroline falling faster than that Christmas Eve snow...